Entrepreneurial attitudes among potential entrepreneurs - Akhtar Ali; Keith J. Topping; Riaz H. Tariq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
This article explores entrepreneurial attitudes among potential entrepreneurs in Pakistan. Multi-stage sampling maximized representation. Four hundred and eighty masters of business administration (MBA) students (potential entrepreneurs) from six public sector Pakistani universities returned completed questionnaires. Three factors emerged: entrepreneurial acceptability, entrepreneurial intentions and personal factors. Moreover, the perceptions of the potential entrepreneurs on locus of control, self efficacy, subjective norms and instrumental readiness were also analyzed. The majority of students showed generally positive attitudes towards entrepreneurship at all six universities. Overall there was a significant difference between negative and positive attitudes (negative mean 184, positive mean 284). There was also some impact of demographic variables, such as university, parental income and profession. Both genders exhibited similar attitudes at most of the sample institutions. The implications for practice and policy are discussed.
Keywords: 330; Entrepreneurial attitude; Masters of Business Administration; Entrepreneurial acceptability; Entrepreneurial intentions; Pakistan; Studierende; Qualifikation; Wirtschaftsstudium; Unternehmensgründung; Pakistan